Native legume species as potential fodder crops in the mediterranean renosterveld shrubland, South Africa. (February 2020) - Chimphango, Samson B.M.; Gallant, Luke H.; Poulsen, Zoe C.; Samuels, M. Igshaan; Hattas, Dawood; Curtis, Odette E.; Muasya, A. Muthama; Cupido, Clement; Boatwright, James S.; Howieson, John
Abstract: The limited grazeable size of renosterveld vegetation in the Western Cape warranted assessment of chemical and fibre composition of the species to determine their nutritive value. We hypothesised that Fabaceae has chemically superior palatable species relative to Poaceae, Asteraceae and Asparagaceae species in the area. Plant samples were collected in the Overberg region from 11 sites. The species sampled from these four families Fabaceae, Poacea e, Asteraceae, and Asparagaceae were analysed for macro- and micro-elements, fibre and secondary compounds. At each site, replicated soil samples were also collected and analysed for pH, macro- and micro-elements. Fabaceae recorded the greatest concentration of crude protein, but the Poaceae was the most fibrous relative to Fabaceae and Asteraceae. All the species contained adequate levels of nutrients except P, Zn and sometimes Cu. Soil concentration of macronutrients and carbon in the soil varied with location. Based on crude protein, neutral detergent fibre and digestibility, the three most important parameters defining forage quality, the Fabaceae species Aspalathus hispida, A. angustifolia, A. nigra and A. submissa were regarded as superior forage species in the Mediterranean renosterveld. Livestock relying on only the renosterveld species in the Western Cape as forages should receive P and Zn supplements. Highlights: Fabaceae recorded greatest concentrations of crude protein and medium to low fibre content . All the species contained adequate levels macro- and micro-nutrients except P, Zn and sometimes Cu. Total phenolic and condensed tannins were low in all species irrespective of plant family. Livestock relying on only the renosterveld species in the Western Cape as forages should receive P and Zn supplements. The Fabaceae species  A. hispida,   A. angustifolia,   A. nigra  and  A. submissa  were superior forage species in renosterveld.